Community Movement in Independent Vegetable Growing to Increase Household Food Security During the Pandemic - Ermita Yusida; Ahmad Fajar Maulidin; Anggi Puspaningrum (Journal of Interdisciplinary Socio-Economic and Community Study, 2021)
The increase in the Covid-19 second wave in Indonesia has made the government implement a stricter policy to implement Community Activity Restrictions (PPKM). This activity aims to provide actionable solutions to maintain family food security through the community movement to grow vegetables. The method used in this activity is the Participatory Rural Appraisal (PRA) method which begins with FGD, counseling, and field practice. The activity implementer can become a facilitator and directly facilitate the community carrying out activities. The empowerment program was carried out in Kepuharjo Village, Malang Regency, with the main target being housewives. As a result of this activity, participants who attended the FGD and the facilitator decided to create a community movement in independent vegetable growing to stay productive during the pandemic. Community movement was conducted for two weeks, during which the activity implementation team provided all materials, planting media, and seeds. During the two weeks running, 53 housewives grew vegetables independently. Based on the evaluation results, this activity is very effective and efficient for household food fulfillment. Ninety-seven percent of homemakers say that they can increase their food needs with this movement, so they don't have to buy. Of course, it has an impact on saving household expenses. As many as 90 percent of homemakers do this activity and repeat it after harvest. So that the continuity of this activity can run well, besides decreasing spending, this activity can also improve health by producing healthier vegetables.